MANAGEMENT OF CHEMISTRY LABORATORY RESOURCES FOR EFFECTIVE TEACHING AND LEARNING CHEMISTRY - KATSAYAL, AMINU BAKO (Sokoto Educational Review, 2025)
Effective management of laboratory resources is crucial for enhancing the quality of chemistry education in secondary schools. Well-equipped and properly managed laboratories provide students with hands-on learning experiences that complement theoretical knowledge, foster critical thinking, and improve academic performance. This paper explores the significance of managing laboratory resources for effective chemistry teaching and learning, identifies common challenges faced by schools (including inadequate funding, poor infrastructure, and a lack of skilled personnel), and proposes strategies for overcoming these obstacles. Key recommendations include increasing funding from both government and private sectors, improving laboratory infrastructure, providing professional development for teachers and technicians, enforcing safety standards, and developing efficient inventory management systems. By addressing these challenges, schools can ensure safe, well-equipped laboratories that support high-quality chemistry education and prepare students for future academic and professional success in the sciences. DOI: https://doie.org/10.0303/SER.2025558386